Postural control strategies in elite freestyle wrestling - Krivoshapkin, P. I.; Rozhin, N. N.; Starostin, E. N. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to contribute to theoretical basics of the postural control biomechanics in modern freestyle wrestling.